Topical Application of Fasudil Hydrochloride for Vasospasm during Soft Tissue Reconstruction Using a Free Flap - Kaoru Tada; Tadahiro Nakajima; Mika Nakada; Masashi Matsuta; Hiroyuki Tsuchiya (Case Reports in Orthopedics)
Vasospasm is a phenomenon that can complicate microsurgery. We report a case in which vasospasm was quickly relieved by topical application of fasudil hydrochloride. A 36-year-old man underwent preoperative chemotherapy and wide excision for a malignant soft tissue tumor around the knee joint. We planned reconstruction using a free latissimus dorsi muscle flap for the resulting soft tissue defect and selected the peroneal vessels as the recipient vessels. However, there was no arterial blood flow from the peroneal vessels, which we diagnosed as vasospasm. Conventional treatment of the vasospasm was attempted, but blood flow was not achieved. Topical application of fasudil hydrochloride solution promptly relieved the vasospasm. To the best of our knowledge, this is the first clinical report of the use of fasudil hydrochloride for vasospasm during soft tissue reconstruction using a free flap.